(untitled) (Лучшие интеллектуальные исследования, 2025)
Chickenpox is one of the most widespread highly contagious infections, with a susceptibility rate of 95-100%. Against the backdrop of decreasing incidence of "controllable" infections, the significance of chickenpox in the structure of infectious pathology increases. Infection with the Varicella Zoster virus (VZV), typically occurring in adulthood, leads to lifelong latent persistence of the pathogen in the body of the person who has recovered from chickenpox, with a high probability of endogenous reactivation years later, often resulting in the development of such severe, debilitating diseases as herpes zoster (shingles) [4,5]. The prevalence is 60 million cases annually. According to the WHO, 4.2 million severe and complicated cases of chickenpox are hospitalized annually, and 4,200 cases lead to death worldwide.